Racial Injustice Reflected In Haper Lee's Go Set A Watchman Novel (2015): A Marxist Criticism - Rahayuningsih, Ibnu Dwy, Titis Setyabudi, M. Hum (2017)
This study aims to examine racial injustice in Go Set a Watchman novel by Harper Lee. This issue raised due to the dominance racial group and racial differences between white and black. Racial injustice which happens can occur in the aspects of social life, Social conditions prevailing in the Go Set a Watchman novel is a racial injustice committed by whites against blacks. The objectives of the study are to describe how racial injustice is reflected in Harper Lee's Go Set a Watchman novel and to explain the causes of racial injustice in Harper Lee's Go Set a Watchman novel. The data are taken from the words, sentences and dialogues in Go Set a Watchman novel. The data are collected by reading, remarking and separating the words, sentences and dialogues in the novel. This research uses Marxist Criticism and the theory of marxist by Antonio Gramsci. The result of the study shows that racial injustice that occurs in Go Set a Watchman novel by Harper Lee happened in three aspects, there are 1) injustice in economic life, 2) injustice in political life, and 3) injustice in legal process. The causes of racial injustice in Harper Lee's Go Set a Watchman novel happened in four aspects, there are racial prejudice, slavery, disparagement, dominance and power.